Social networking in higher education in India - Issa, Tomayess; Malleshappa, A. (Springer, 2018)
Innovations in technology are remarkable as they enable people to be reached almost immediately. This is the beauty and uniqueness of technology as it makes visual communications so easy. The emergence of the Internet is the main reason for further innovations in technology since the world is being interconnected with the web. The web technologies have made the world connect more closely and enabled people to interact by sharing experiences and information. Social networks are integrated with the cognitive aspects of human beings. It makes the technology even better by combining the hardware of the computer with the feelings of human beings. Social networks have grown like never before but are they acceptable in all the sectors? Well, each stream has its own perspective concerning social networks. Higher education is one of those streams, which uses social networking in huge numbers. Educational institutions have been in the process of providing a career path to its students through guidance and recognizing their skills. Social networks would help the education providers by making this much easier by providing platform enabling them to know more about their students. The primary objective of this research is to examine the advantages and disadvantages to students that arise when using social networks and to validate the importance of social networking in education. This research intends to list the advantages that Indian students and educational institutions can take advantage of in the academic environment via using social networking, and to list the disadvantages to help the policy makers and students to be well aware of the negative situations that they might encounter by using social networking in the Indian higher education. The research uses a quantitative method, in this case an online survey, as its main approach. 103 participants completed the online survey from 175 participants. Finally, this study was limited to India higher education, further research will be carried out in the future to examine other higher education from developed and developing countries.